PHYTOSANITARY CONTAMINATION IN SEA CONTAINERS - Eslava Sarmiento, Alexander
Unprecedent rates of introduction and spread of non-native species pose increasing challenges tobiodiversity, natural resource management and regional economies. Globalization in terms of transportand international trade in goods have compromised the natural biogeographical and ecological barriersbetween countries and continents through the transport of pests that contributes to their establishment in anew ecosystem. Changing global economic forces determine the volume of trade and the frequency withwhich ships transit between ports of origin and destination. Annually, more than 800 million sea containersare moved globally, facilitated by efficient logistics flow through world trade supply chains. Themovement of containerized goods from one country to other carries the risk of transferring phytosanitarypests to the ecosystems of the destination countries; these unwanted organisms get into the goods inside thecontainer, into the materials in which the goods are packed, and into the container itself. International tradeis the vector, maritime containers the vehicle; Once introduced, the phytosanitary pest is very difficult andexpensive to control and eradicate.